Endogenous bufadienolides, mineralocorticoid receptor antagonists and fibrosis in chronic kidney disease - Rosenberg, Mai; Bagrov, Alexei Y. (Frontiers in Pharmacology, 2024)
Every year millions die prematurely of complications related to chronic kidney disease (CKD). Main causes of death are connected with cardiovascular (CV) complications. There is no cure for CKD although current treatment can slow the progression of the disease if diagnosed early. Fortunately, last decades have witnessed an accelerating pace of discovery regarding the cellular and molecular basis for CKD and CV disease. Novel biomarkers, including amino-terminal type III procollagen peptide (PIIINP), carboxy-terminal type I procollagen peptide (PICP), FGF23, marinobufagenin, and several miRNAs, show promise for early detection and risk stratification. In this review, we provide an overview of recent advances in the "fibrotic concept" of the etiology and pathogenesis of CKD which involves system consisting of Na/K-ATPase and its endogenous ligands including marinobufagenin which inhibits Fli1 and stimulates synthesis of collagen-1 in the vasculature. A novel treatment of CKD already involves the use of mineralocorticoid receptor antagonists capable of impairing marinobufagenin-Na/K-ATPase interactions.